The politics of sexual harassment : a comparative study of the United States, the European Union, and Germany - Zippel, Kathrin S. (Cambridge University Press, 2006)
Sexual harassment, in particular in the workplace, is a controversial topic which often makes headline news. What accounts for the cross-national variation in laws, employer policies, and implementation of policies dealing with sexual harassment in the workplace? Why was the United States on the forefront of policy and legal solutions, and how did this affect politicization of sexual harassment in the European Union and its member states? Exploring the way sexual harassment has become a global issue, Kathrin Zippel draws on theories of comparative feminist policy, gender and welfare state regimes, and social movements to explore the distinct paths that the United States, the European Union and its member states, specifically Germany, have embarked on to address the issue. This comparison provides invaluable insights on the role of transnational movements in combatting sexual harassment, and on future efforts to implement the European Union Directive of 2002.